2013
DOI: 10.1158/1535-7163.mct-12-0603
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Tumor Regression Induced by an Antibody–Drug Conjugate That Targets 5T4, an Oncofetal Antigen Expressed on Tumor-Initiating Cells

Abstract: Antibody-drug conjugates (ADC) represent a promising therapeutic modality for the clinical management of cancer. We sought to develop a novel ADC that targets 5T4, an oncofetal antigen expressed on tumorinitiating cells (TIC), which comprise the most aggressive cell population in the tumor. We optimized an anti-5T4 ADC (A1mcMMAF) by sulfydryl-based conjugation of the humanized A1 antibody to the tubulin inhibitor monomethylauristatin F (MMAF) via a maleimidocaproyl linker. A1mcMMAF exhibited potent in vivo ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 29 publications
5
89
0
Order By: Relevance
“…In the low-5T4-expressing cell line, MDAMB468, A1 HC-S115pAF-NC-D1 is twofold more potent than conventional A1 mc-D1. The significant difference in the in vitro potency between 3+ (MDA MB435/5T4, cells expressing high levels of 5T4) and 2+ (MDA MB468, endogenously expressed 5T4) is likely due to different levels of 5T4 expression in the two cell lines (25).…”
Section: Resultsmentioning
confidence: 99%
“…In the low-5T4-expressing cell line, MDAMB468, A1 HC-S115pAF-NC-D1 is twofold more potent than conventional A1 mc-D1. The significant difference in the in vitro potency between 3+ (MDA MB435/5T4, cells expressing high levels of 5T4) and 2+ (MDA MB468, endogenously expressed 5T4) is likely due to different levels of 5T4 expression in the two cell lines (25).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed protocols to determine the affinity of mAb A1 towards 5T4 antigen and internalization rate of surface bound mAb in 5T4 expressing cell is presented in the supplementary material of (4). Briefly, Biacore® analysis was performed to determine the binding constants between A1 and 5T4 at pH 7.4.…”
Section: Affinity and Internalization Of A1mcmmafmentioning
confidence: 99%
“…The anti-5T4 ADC is termed A1mcMMAF and comprises the humanized anti-5T4 antibody (A1) linked to the potent microtubule-disrupting agent monomethylauristatin F (MMAF) a noncleavable maleimidocaproyl (mc) linker. A1mcMMAF has been shown to be highly potent in a variety of tumor models and did not cause any overt toxicity in nonhuman primates at comparable exposures (4). As such, A1mcMMAF is a promising clinical candidate that targets TICs, with the goal of providing long-term therapeutic benefit to patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these findings suggested that therapy could be enhanced by targeting TM4SF1 with an ADC approach. ADCs have entered the clinic and are currently used to target tumors expressing many different antigens, including CD33 (40), Her2 (41), and CD30 (42); more than 100 additional ADCs directed against different tumor cell targets populate the preclinical and clinical pipelines (43)(44)(45)(46). An ADC against a target expressed by both tumor cells and the tumor vasculature would be expected to offer exceptional therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%